2018
DOI: 10.1007/s11938-018-0197-8
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer and Diabetes Mellitus

Abstract: Studies report that while some anti-diabetic medications (e.g., metformin) may decrease the risk of PDAC, others (insulin, sulfonylureas and incretin-based therapies) may increase the risk. However, these observations may be subject to protopathic biases. Metformin's anti-tumor activity may have influence overall survival of PDAC, but epidemiological reports have largely been inconsistent to defend these findings due to heterogeneous methodologies. There is congruent data to support the association between DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
0
27
0
6
Order By: Relevance
“…T2DM was shown to be an independent risk factor for pancreatic cancer in many studies [273][274][275][276][277][278] and some authors have implicated hyperglycemia in cancer pathogenesis [279,280]. However, inferring causality for this observation is further complicated by the fact that PDAC itself and PDAC treatment regimens can cause diabetes [281][282][283]. Nevertheless, a Mendelian randomization study pointed to causal roles for BMI and fasting insulin, but not T2DM or dyslipidemia, in PDAC [284].…”
Section: Hyperinsulinemia and Pancreatic Cancermentioning
confidence: 99%
“…T2DM was shown to be an independent risk factor for pancreatic cancer in many studies [273][274][275][276][277][278] and some authors have implicated hyperglycemia in cancer pathogenesis [279,280]. However, inferring causality for this observation is further complicated by the fact that PDAC itself and PDAC treatment regimens can cause diabetes [281][282][283]. Nevertheless, a Mendelian randomization study pointed to causal roles for BMI and fasting insulin, but not T2DM or dyslipidemia, in PDAC [284].…”
Section: Hyperinsulinemia and Pancreatic Cancermentioning
confidence: 99%
“…More than two-thirds of individuals with pancreatic cancer have diabetes or prediabetes (11). Some populationbased studies showed a significantly lower mortality risk associated with the use of metformin (12)(13)(14)(15)(16), whereas others (17)(18)(19) found no significant survival benefit of metformin in individuals with PCRD.…”
mentioning
confidence: 99%
“…Unfortunately, even in this case, no definitive conclusions have as yet been reached. It is not entirely clear whether, how much, and in which direction diabetes treatments affect the association between diabetes and PDAC [ 23 , 25 , 64 , 65 , 66 , 67 ]. To give a couple of examples, the protection provided by metformin, the most commonly drug used to treat T2DM, is currently under vigorous discussion, together with its mechanistic implications [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and even the increased risk of PDAC observed in insulin-treated patients in some case-control studies [ 27 , 74 ] can be misleading [ 26 , 72 ].…”
Section: Relationship Between Diabetes and Pancreatic Cancermentioning
confidence: 99%